Job insecurity to counter productive work behavior moderated leader-member exchange - Yuni Siswanti (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Purpose – This study aims to find out and analyze the influence of job insecurity on counterproductive work behavior (CWB) and test the quality of LMX as a variable moderation in employees in the creative culinary in Sleman Regency Yogyakarta. Design/Methodology/Approach – The type of research used in this study is explanatory with a quantitative approach. The population of this study is employees in 18 creative industries in the culinary field in Sleman Regency, Yogyakarta. One hundred twenty-two respondents took the sample by the purposive method. The instrument Test used validity and reliability. Hypothesis testing uses simple regression and moderated regression. Findings – Results show that job insecurity significantly affects counterproductive work behavior (CWB). LMX quality moderates the effect of job insecurity on CWB. The results of this study have theoretical and managerial implications and require further research. Research Limitation/Implications – This study has limitations, namely: population collection is still minimal because SMEs are studied in only one district, the type of SMEs business and limited to culinary, cross-sectional data collection. Further research should be expanded in the scope of the population, not only in one district but expanded in other districts in Yogyakarta. The type of product produced by respondents in this study is the culinary field, so it should be extended to different SMEs types. Second, cross-sectional data collection of this study requires a more longitudinal design in the future to get better study results. Third, the study did not distinguish CWB in workers with permanent employee status and workers with contract employee status. Practical Implications – Providing understanding to culinary SMEs to maintain good relations with all workers in the form of respecting workers, respect for the work of the men, establishing effective communication with workers under any conditions, trying their best for their men, and increasing the sense of belonging in the men. Theoretical Implications – Academics and researchers have a perceptual understanding of the contribution of leader-member relationships (LMX) in lowering the influence of job insecurity on CWB (CWB-O) and (CWB-I). Originality/Value – Authenticity of the study: Previous research that included LMX quality as a moderation variable between job insecurity and CWB is still very minimal. It shows that the theory reinforces the existence of LMX Theory that the high quality of LMX between leader-members has been characterized by an exchange of emotions based on mutual trust and respect. In contrast, the low quality of LMX relationships has the characteristics of economic exchange.